INVASION OF RIPARIAN HABITATS BY BUDDLEJA DAVIDII: A CASE STUDY FROM THE NORTHERN APENNINES - Gasperini, C.; Carrari, E.; Selvi, F. (Annali di Botanica, 2020)
Buddleja davidii Franch. is one of the most aggressive invasive plants across the world, especially in riparian ecosystems. However, the invasion processes and the impacts of this species are still poorly known. Here we report a case of massive invasion in the valley of a montane stream of the Tusco-Emilian Apennines, started around the year 1990. In this study, the species was recorded along a corridor of 4.3 km, representing 60% of the total streambed length. Invasion intensity was low in the early herbaceous stage of the succession, while it was highest in the woody pre-forest stage with Salix eleagnos and S. purpurea. Intermediate intensity occurred in the riparian forest with Alnus incana. Plot-level Shannon diversity and evenness of these plant communities were negatively related to B. davidii cover, as well as abundance of woody and herbaceous species. Hence, our findings indicate a negative impact on the diversity of local riparian vegetation. Minimizing the human-mediated disturb to the riparian habitat may help to limit the spread of this alien species in similar habitats of the area.